Study The Effect of The Distance Changes Between The Camera and The Object on The Accuracy of Images Orientation in Automated Photogrammetry - الخليل عمر; يحي منير; دوه جي محمد (Latakia University Journal -Engineering Sciences Series, 2020)
In this research, the accuracy of images orientation resulted from Structure-from-Motion (SfM) method was evaluated to determine whether the distance had an important effect on this accuracy and to know the pattern of this accuracy if there was any effect of the distance.Because of the limited breadth of the experiment, a rotating disk was designed and used to simulate the state in which the camera moves around the object. Multiple images were taken from different distances and the corresponding point cloud was generated for each distance using Agisoft Metashape. Availability of this number of point clouds allowed to perform the accuracy evaluation process.Images were taken from all distances using the same calibration camera and with the same lighting conditions as well as the same control points in terms of number and distribution in order to isolate the effect of another factor on the accuracy of the point clouds resulting from these images and to keep the effect of distance change only